2010
DOI: 10.1002/jor.21227
|View full text |Cite
|
Sign up to set email alerts
|

Metaphyseal fracture healing follows similar biomechanical rules as diaphyseal healing

Abstract: ABSTRACT:It is generally supposed that the pattern of fracture healing in trabecular metaphyseal bone differs from that of diaphyseal fractures. However, few experimental studies to date have been performed, even though clinically many fractures occur in metaphyseal bone. Particularly, the influence of biomechanical factors has not yet been investigated under standardized conditions. Our aim was to correlate the interfragmentary strain (IFS) with the bone-healing outcome in a controlled metaphyseal fracture mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 18 publications
3
63
0
1
Order By: Relevance
“…Nonunions remain a considerable complication following femoral neck fracture treatment (Parker et al 2007). From animal experiments we know that magnitude of interfragmentary motion is important for the course of fracture healing (Perren 2002, Augat et al 2005, Claes et al 2011. Our experiment revealed that micromotions about the femoral neck (z-axis) were significantly reduced in the locking plate group, representing an improved resistance to shear forces.…”
Section: Study IImentioning
confidence: 63%
See 1 more Smart Citation
“…Nonunions remain a considerable complication following femoral neck fracture treatment (Parker et al 2007). From animal experiments we know that magnitude of interfragmentary motion is important for the course of fracture healing (Perren 2002, Augat et al 2005, Claes et al 2011. Our experiment revealed that micromotions about the femoral neck (z-axis) were significantly reduced in the locking plate group, representing an improved resistance to shear forces.…”
Section: Study IImentioning
confidence: 63%
“…The epiphyseal plate itself is considered part of the metaphysis which follows the same principles of fracture healing as diaphyseal bone (Claes et al 2011). Fracture healing is a complex process dependent on numerous local and systemic factors and only a brief description will be given in this thesis.…”
Section: Fracture Healingmentioning
confidence: 99%
“…Cartilage formation might be related to low oxygen tension. Instability, or rather micromotion, will induce cartilage formation in both cancellous and cortical healing [17][18][19][20][21][22][23][24]. However, cancellous fractures are generally stable in the sense that repeated cyclic deformation of a considerable magnitude is unlikely to occur.…”
Section: Endosteal Cells Are Prone To Direct Membranous Formationmentioning
confidence: 99%
“…A slight cyclic deformation has been showed to be beneficial for optimal bone formation in traumatized cancellous bone both in humans and animals [17,25,26].…”
Section: Endosteal Cells Are Prone To Direct Membranous Formationmentioning
confidence: 99%
“…There is a myriad of papers on the biology of shaft fracture healing, but only a very sparse literature on the biology of cancellous bone fractures. 6 This might be due to the paucity of animal models for cancellous bone healing, especially for mechanical evaluation.…”
Section: Introductionmentioning
confidence: 99%